Cash transfer, maternal and child health outcomes: a scoping review in sub-Saharan Africa - Emery L. Ngamasana; Jessamyn Moxie (Global Health Action)
Background Cash Transfer (CT) programmes can improve maternal and child health outcomes in low- and middle-income countries. However, studies assessing the effectiveness of these programmes on maternal and child health outcomes (MCH), beyond nutritional outcomes and service utilisation, remain inconclusive. Objectives We synthesized current empirical evidence on the effectiveness of these programmes in improving MCH outcomes and suggested a framework for reporting such outcomes. We focused on sub-Saharan Africa because of substantial operational differences between regions, and the need for MCH advancement in this region. Methods This review searched PubMed Central and Google Scholar and supplemented it with a backward citation search for studies conducted in sub-Saharan Africa for the period between 2000 and 2021. Only peer-reviewed studies on CT that reported health outcomes beyond nutritional outcomes and service utilisation among women of reproductive age and children below 18 years old were included. Results Twenty-one articles reporting studies conducted in six sub-Saharan African countries were identified. All studies reported health outcome measures, and programmes targeted women of reproductive age and children under 18 years of age. Of the 21 articles, 1 reported measures of mortality, 13 reported measures of functional status; 3 reported subjective measures of well-being, and 4 reported behavioural health outcomes. Across all categories of reported measures, evidence emerges that cash transfer programmes improved some health outcomes (e.g. improved infant and child survival, reduced incidence of illnesses, improved cognitive and motor development, improved general health, delayed sexual debut, lower transactional sex, etc.), while in some of the studies, outcomes such as depression did not show significant improvements. Conclusion Cash Transfer programmes are effective and cost-effective, with a real potential to improve maternal and child health outcomes in sub-Saharan African countries. However, further research is needed to address implementation challenges, which include data collection, and programme management.